Penyuluhan Pendidikan Karakter Adaptasi Thomas Lickona - Damariswara, Rian; Wiguna, Frans Aditia; Khunaifi, Abdul Aziz; Zaman, Wahid Ibnu; Nurwenda, Dhian Dwi (Universitas Nusantara PGRI Kediri, 2021)
Counseling on character education adaptation of Thomas Lickona at SDN Gayam 3 is a community service that aims to provide information on the importance of character education in elementary schools and collect information on the implementation of character education at SDN Gayam 3. three aspects, namely knowledge (moral knowing), feelings (moral feeling), and action (moral action). These three aspects are coherent and comprehensive. All three are interconnected and used together. In addition, in the question and answer activity, it was stated that Huru had carried out character education as stated by Thomas Lickona, but did not know that there was a theory. In addition, character education is not only the responsibility of the teacher, but also the responsibility of parents and the environment in which students live. This is known as the tri education center.